Pelatihan Programmable Logic Controller (PLC) Bagi Siswa Smk Muhammadiyah 1 Ponorogo - Didik Riyanto (ADIMAS Jurnal Pengabdian Kepada Masyarakat, 2017)
This program is focused in programmable logic controller (PLC) training at SMK Muhammadiyah 1 Ponorogo  students majoring electronics or audio video. The training concept includes introduction and programming of  PLC with the expectation that the students of SMK Muhammadiyah 1 Ponorogo who attended training obtain automation skills, especially in automation PLC. The skills could be a provision for the students after graduated or in the workkplace. The training was conducted in the laboratory of electrical engineering PLC Muhammadiyah University of Ponorogo by lectures and experts in PLC. Eelectrical engineering in Muhammadiyah Uuniversity of Ponorogo is one of the universities in East Java which has a laboratory automation system PLC with national university standard that provides knowledge for profesional staff in the field of automation